Estuarine circulation-driven entrainment of oceanic nutrients fuels coastal phytoplankton in an open coastal system in Japan. (5th January 2017) - Watanabe, Kenta; Kasai, Akihide; Fukuzaki, Koji; Ueno, Masahiro; Yamashita, Yoh
Abstract: We investigated interactions among seasonal fluctuations in phytoplankton biomass, riverine nutrient flux, and the fluxes of nutrients entrained by estuarine circulation in Tango Bay, Japan, to determine the influence of freshwater inflows to an open bay on coastal phytoplankton productivity. The riverine nutrient flux was strongly regulated by river discharge. Estuarine circulation was driven by river discharge, with high fluxes of nutrients (mean nitrate + nitrite flux: 5.3 ± 3.5 Mg [mega grams]-N day −1 ) between winter and early spring, enhanced by nutrient supply to the surface water via vertical mixing. In contrast, low-nutrient seawater was delivered to the bay between late spring and summer (1.0 ± 0.8 Mg-N day −1 ). Seasonal fluctuations in phytoplankton biomass were affected by the entrained fluxes of oceanic nutrients and variation in the euphotic zone depth, and to a lesser degree by the riverine nutrient flux. Bioassays and stoichiometric analyses indicated that phytoplankton growth was limited by nitrogen and/or phosphorus. Both the entrainment of oceanic nutrients and the euphotic zone depth affected the duration and magnitude of blooms. Our findings show that, unlike semi-enclosed bays, seasonal variations in coastal phytoplankton in an open coastal system are primarily fueled by the entrainment of oceanic nutrients and are influenced by both freshwater inflow and coastal conditions (e.g. vertical mixing and wind events). Highlights: Interactions among seasonal changes in phytoplankton, nutrient fluxes, and light availability were examined in an open bay. Phytoplankton was affected by the entrained fluxes of oceanic nutrients and variation in the euphotic zone depth. Phytoplankton is primarily fueled by the entrainment of oceanic nutrients driven by estuarine circulation in the open bay.